THE ROLE OF TRAINING AND MANAGEMENT IN THE SYSTEM OF DEMAND-SUPPLY IN THE TOURISM OF MOZAMBIQUE - Darabos, Ferenc (PEOPLE: International Journal of Social Sciences, 2019)
Nowadays with migration issues, the increasing enmity between the north and the south, the analysis of the economic cutch-up of developing countries is becoming more and more relevant under the principle “think globally and act locally”. In our research this year – based on our personal relationship – we have chosen to analyse tourism in Africa, in particular, Mozambique. Our main theme focuses on the role of training and management, because we believe that among the elements necessary for an economic catch-up to achieve significant results these two elements need to be developed. Based on the number of employees in the tourism sector (271 300 people) the country occupies the 51st place in the world which is not bad compared to its contribution to the GDP. The export generated by foreign tourists from 2008 to 2017 doubled (180 million USD) but the country is behind the frontline. In our research we have analysed the importance of the demand related to tourism. First we sought answers to the questions how efficient and useful is the potential found in the current workforce compared to that of the competitors, what problems overwhelm the sector’s management and what are the barriers to development. We were also interested in how the sector’s training supports the innovation of tourism. To answer the questions above, we conducted a primary research after carrying out an interview with the leadership of Escola Superior de Hotelaria e Turismo de Inhambane (College of Catering and Tourism of Inhambane) where we enquired about the role of training and management. This school is academically controlled by Universidade Eduardo Mondlane (University Eduardo Mondlane) located in Maputo. Besides evaluating the information gained through the interview we also analysed and compared the existing and the obtained data and information.